Sensory Attributes of Jackfruit: A beyond Meat Sandwich Filling - Florence Ojiugo Uruakpa; Ruchithri Nanayakkara; Lauren Pavel; Tessa Robinett (Journal La Lifesci, 2021)
Jackfruit is used as a meat substitute by some consumers but reports on its use are scanty. Jackfruit is becoming popular among meat lovers who want non-soy-based meat alternative. Thus, this study aims to 1) discover a healthy and affordable option to meat and 2) assess if consumers candifferentiate between pulled pork and jackfruit in a sandwich. Three types of sandwiches were prepared (i.e., jackfruit-in-water; pork tenderloin; jackfruit-inbrine). Sensory analysis using 300 untrained panelists was conducted to examine selected quality attributes (flavor, texture, aroma) and identify the meat-based sample. Panelists scored the sandwiches on a scale of 1-3 with 1 being most favored. The mean scores were calculated as follows: pork = 1.54), jackfruit in brine = 2.16), and Jackfruit in water = 2.18. Statistical analysis (2 tailed T-test) found a significant difference (p = 0.003) in flavor between thepork sandwich (score = 1.6) and those of jackfruit in brine (score = 2.17) and water (score = 2.17). There was a significant difference (p = 0.05) in the texture of pork sandwich (score = 1.6) and jackfruit sandwich in brine (score = 2.0) and water (score = 2.3). Most tasters thought the jackfruit was a meat product although the meat product was ultimately favored. Participants did not know that the sandwiches had a meat substitute. Jackfruit could be a desirable meat substitute for consumers who are looking for low-fat meat alternative rich in antioxidants to add to meals.